2020
DOI: 10.3390/ma13061362
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Basic Mechanical Properties of Basalt Fiber Reinforced Concrete

Abstract: Blending a certain proportion of basalt fiber into concrete improves the toughness of concrete, which prevents cracking and avoids the brittle behaviors. In this paper, the compressive, tensile, and flexural tests of concrete with different basalt fiber contents were carried out. Then the test phenomena, failure modes, and mechanical properties were compared and analyzed to derive the relationship between the basalt fiber contents and mechanical properties. The toughness and crack resistance performance of bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(47 citation statements)
references
References 33 publications
0
44
0
3
Order By: Relevance
“…Fibres that are most commonly used to reinforce mortars are made of steel, carbon, glass, polypropylene and basalt [ 41 , 42 , 43 , 44 ], although the use of other natural fibres, such as sisal, has also been reported [ 45 ]. As the basalt fibres used in this study are a relatively new material [ 46 , 47 , 48 , 49 , 50 ], the properties of composite materials (including cementitious mortars) with their addition have not been fully discovered yet, and intensive research is still recommended [ 42 ]. A summary of the studies carried out thus far on various types of mortars with the addition of basalt fibres was presented in [ 51 ], where the authors suggested the following.…”
Section: Introductionmentioning
confidence: 99%
“…Fibres that are most commonly used to reinforce mortars are made of steel, carbon, glass, polypropylene and basalt [ 41 , 42 , 43 , 44 ], although the use of other natural fibres, such as sisal, has also been reported [ 45 ]. As the basalt fibres used in this study are a relatively new material [ 46 , 47 , 48 , 49 , 50 ], the properties of composite materials (including cementitious mortars) with their addition have not been fully discovered yet, and intensive research is still recommended [ 42 ]. A summary of the studies carried out thus far on various types of mortars with the addition of basalt fibres was presented in [ 51 ], where the authors suggested the following.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the related researches show that BF enhances the toughness, impermeability, and preventing cracks of concrete 38 – 41 . Zhou 42 indicated that BF enhanced effect on the compressive strength, tensile strength, and flexural strength. The improvement effect was the highest with the basalt fiber content was 0.3% and 0.4%.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with steel fiber and carbon fiber, BF has the advantages of excellent mechanical properties, outstanding thermal properties, stable chemical properties, and excellent compatibility. Therefore, the study of BFRC has certain theoretical significance and practical value, and also plays an important guiding role in improving the performance of concrete [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%